2021
DOI: 10.1021/acs.orglett.1c02645
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Monoborylation of Spirocyclobutenes

Abstract: We present a strategy for the synthesis of spirocyclic cyclobutanes with modulable exit vectors based on the regioselective monoborylation of spirocyclobutenes. Using an inexpensive copper salt and a commercially available bidentate phosphine, a broad variety of borylated spirocycles have been prepared with complete regiocontrol. The boryl moiety provides a synthetic handled for further functionalization, allowing access to a wide array of spirocyclic building blocks from a common intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Under related conditions using achiral ligand 1,1′-bis(diphenylphosphino)ferrocene (dppf), the achiral, spirocyclic cyclobutane 6 is obtained from 5 as a single regioisomer ( Scheme 2 ). 31 Good yields were obtained with a small set of functionalized salicylaldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…Under related conditions using achiral ligand 1,1′-bis(diphenylphosphino)ferrocene (dppf), the achiral, spirocyclic cyclobutane 6 is obtained from 5 as a single regioisomer ( Scheme 2 ). 31 Good yields were obtained with a small set of functionalized salicylaldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…Following a recent metal-free base-catalyzed diboration of spirocyclic cyclobutenes, Tortosa and co-workers disclosed a regioselective Cu-catalyzed protoboration of the same substrate class. 48 Here, the authors examined several NHC and phosphine ligands and showed that the Cu−Xantphos catalytic system can promote Cu-boryl addition with exclusive regioselectivity (Scheme 36). Different functional groups and spirocycle ring sizes were tolerated.…”
Section: Reactionsmentioning
confidence: 99%
“…The preparation of borylated cyclobutanes is particularly desirable, as the boron moiety acts as a convenient synthetic handle for further elaboration via a range of C–C, 3 C–N, 4 C–O, 5 or carbon–halogen 6 bond forming processes. Current strategies to synthesize borylated cyclobutanes typically fall into four broad categories: (a) [2 + 2]-cycloadditions, 7 (b) strain release/increase reactions, 8 (c) C–H functionalizations, 9 and (d) borylmetalation of alkenes 10 ( Scheme 1a ). 11 While significant work has gone towards the development of these methods, they often require starting materials that are not readily available and/or already contain the cyclobutane core.…”
mentioning
confidence: 99%